The Moderating Role of Psychological Well-Being on The Relationship Between Psychological Capital and Job Satisfaction - Legowati, Maria Asri; Mustika, Martina Dwi (GoAcademica Research & Publishing, 2024)
There has been a lot of research on job satisfaction recently. Employees who are satisfied with their job will have an impact on their job performance. This study aimed to determine the moderating role of Psychological Well-Being on the relationship between Psychological Capital and Job Satisfaction. Participant in this study is 207 employees of an X coal mining company in Indonesia. The measuring tools used were Psychological Well Being Scale (Ryff et al., 1995), Psychological Capital Questionnaire (Luthans et al., 2007), and Michigan Organization Assessment Questionnaire Job Satisfaction Sub Scale (Camman, et al., 1979). The result of the analysis data show that there was a relationship between psychological capital and job satisfaction, and psychological well-being had no moderating effect on the relationship between psychological capital and job satisfaction.